Calcineurin-independent NFATc1 signaling is essential for survival of Burkitt lymphoma cells - Murti, Krisna; Fender, Hendrik; Glatzle, Carolin; Wismer, Rhoda; Sampere-Birlanga, Salvador; Wild, Vanessa; Muhammad, Khalid; Rosenwald, Andreas; Serfling, Edgar; Avots, Andris (Frontiers in Oncology, 2023)
In Burkitt lymphoma (BL), a tumor of germinal center B cells, the pro-apoptotic properties of MYC are controlled by tonic B cell receptor (BCR) signals. Since BL cells do not exhibit constitutive NF-B activity, we hypothesized that anti-apoptotic NFATc1 proteins provide a major transcriptional survival signal in BL. Here we show that post-transcriptional mechanisms are responsible for the calcineurin (CN) independent constitutive nuclear over-expression of NFATc1 in BL and Eµ-MYCinduced B cell lymphomas (BCL). Conditional inactivation of the Nfatc1 gene in B cells of Eµ-MYC mice leads to apoptosis of BCL cells in vivo and ex vivo. Inhibition of BCR/SYK/BTK/PI3K signals in BL cells results in cytosolic re-location of NFATc1 and apoptosis. Therefore, NFATc1 activity is an integrated part of tonic BCR signaling and an alternative target for therapeutic intervention in BL.